Reactivity and Microstructure of Al2O3-Reinforced Magnesium-Matrix Composites - Maher Mounib; Matteo Pavese; Claudio Badini; Williams Lefebvre; Hajo Dieringa (Advances in Materials Science and Engineering)
Performances of metal matrix composites (MMCs) rely strongly on the distribution of particles within the metal matrix but also on the chemical reaction which may occur at the liquid-solid interfaces. This paper presents the chemical reaction between aluminum based particles Al2O3 and Al2O3-AlOOH with magnesium alloys matrixes AZ91 and EL21, respectively, and studies the microstructure of these reinforced composites. Different methods such as transmission electron microscopy (TEM), differential scanning calorimetry (DSC), and XRD were used to highlight these chemical reactions and to identify products. Results demonstrate the formation of MgO particles within the matrix for both composites and also the dissolution of aluminum in the eutectic region in the case of EL21.